THE INTERPRETATION OF DUALISM - RODRIGUEZ, EDUARDO; BALDWIN, JAMES MARK (Departamento de Salubridad, CD MEXICO, DF, MEX, 1913)
chapter- Discusses the interpretation of dualism during the first and second periods of modern psychology (PsycINFO Database Record © 2008 APA, all rights reserved)
Keywords: INTERPRETATION, DUALISM; FILOSOFIA; FILOSOFIA DEL CONOCIMIENTO